Vonnegut Reinvented - Nandori, Rita (Hungarian Journal of English and American Studies, 2021)
Book review: McInnis, Gilbert. Kurt Vonnegut, Myth and Science in the Postmodern World. New York: Peter Lang Publishing, 2020. 184 pages. ISBN 978-1-4331-7435-3. Hb. CAD 42.08.